HARGA DIRI DAN AGRESIVITAS PEMBALAP LIAR - Fitrah Imanuddin; Burhanuddin Tola (Journal of Research and Measurement in Psychology, 2017)
The objectives of this research is to find out self esteem and aggressivity of illegal motorcycle racing that are: profile of illegal motorcycle racers who always make agressivity, factors which cause illegal motorcycle racers do the activities of illegal motorcycle racing, self esteem of illegal racers who always make agressivity, and the impact of self esteem towards illegal motorcycle racers. This research uses a qualitative approach with a case study method of two illegal motorcycle racers who have ten years experience in doing illegal motorcycle racing. This case study was conducted in Bekasi, West Java and Special Jakarta Province starting from 22 October until 22 December 2012. Data was gained through observation and indepth interview. The data was triangulated through crosscheck with all information from other sources before it was analysed qualitatively, i.e. classification of data, coding, examining of the hypothesis, interpretation, and conclusion. The findings of the research are: 1) both illegal racers have two self esteem and aggressivity eventhough they have different indicators, 2) factors causes illegal motorcycle racers who do the illegal motorcycle racing in order to be famous, more respectful and not despiced by other people, have a support from friend, as a kind hobby, and interested in doing challenge referring to the adrenalin, 3) self esteem of illegal motorcycle racers caused their aggresivity due to their self defend, and 4) the impactof self esteem of illegal motorcycle racers is that arise aggressivity, and damaging themselves, society, and other illegal motorcycle racers.